The relationship between the logistics complexity of manufacturing companies and their supply chain management - Peter Fernandes Wanke; Henrique Luiz Corrêa (Production)
This study aims to investigate whether, and the means by which, supply chain managers of large manufacturing companies adopt a context-dependent approach (also called contingency approach) in their supply chain decisions; it empirically explores the correlation between logistics complexity-related contextual conditions and supply chain management (SCM) objectives and decision areas. The study involves a comprehensive literature review, followed by an analysis of survey data (based on a sample of 108 large manufacturing companies in Brazil), using cluster analysis, factor analysis and binary logistic regression. In this study, we not only investigate the major effects of supply chain objectives and decision areas as predictors of the logistics complexity of manufacturing but also investigate their second order interactions. Statistically significant relationships were found between logistics complexity-related contextual conditions and objectives and decision areas involving the supply chain. The managers of large companies who were surveyed considered different objectives and decision areas to be critical to the achievement of supply chain excellence when their companies had different levels of logistics complexity.